Cbf11 and Cbf12, the fission yeast CSL proteins, play opposing roles in cell adhesion and coordination of cell and nuclear division - Prevorovský, Martin; Grousl, Tomás; Stanurová, Jana; Rynes, Jan; Nellen, Wolfgang; Půta, Frantisek; Folk, Petr (Experimental cell research, 2009)
The CSL (CBF1/RBP-Jkappa/Suppressor of Hairless/LAG-1) family is comprised of transcription factors essential for metazoan development, mostly due to their involvement in the Notch receptor signaling pathway. Recently, we identified two novel classes of CSL genes in the genomes of several fungal species, organisms lacking the Notch pathway. In this study, we characterized experimentally cbf11+ and cbf12+, the two CSL genes of Schizosaccharomyces pombe, in order to elucidate the CSL function in fungi. We provide evidence supporting their identity as genuine CSL genes. Both cbf11+ and cbf12+ are non-essential; they have distinct expression profiles and code for nuclear proteins with transcription activation potential. Significantly, we demonstrated that Cbf11 recognizes specifically the canonical CSL response element GTGA/GGAA in vitro. The deletion of cbf11+ is associated with growth phenotypes and altered colony morphology. Furthermore, we found that Cbf11 and Cbf12 play opposite roles in cell adhesion, nuclear and cell division and their coordination. Disturbed balance of the two CSL proteins leads to cell separation defects (sep phenotype), cut phenotype, and high-frequency diploidization in heterothallic strains. Our data show that CSL proteins operate in an organism predating the Notch pathway, which should be of relevance to the understanding of (Notch-independent) CSL functions in metazoans.
Keywords: biologické modely; Models, Biological; signální transdukce; Signal Transduction; buněčná adheze; Cell Adhesion; Cell Nucleus Division; Schizosaccharomyces pombe Proteins; Schizosaccharomyces pombe - proteiny; Schizosaccharomyces; dělení bunečného jádra